(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
This paper is the start of a larger work in progress, and is based on personal experience, professional experience as an adult educator, and ongoing investigative research. It argues that the historic events in Ireland in Easter 1916 were overtly and covertly subjugated as a discourse in Scotland; brought under the yoke and made subservient to dominant discourses of the British State. With the linguistics of the actual 1916 Proclamation of the Irish Republic in mind, I place emphasis on a key and insightful definition of discourse by Edwards & Usher (1994: 08): ‘discourse defines what can be said, which is based on what cannot be said, on what is marginalised and repressed.’ The paper, then, is the result of semi-structured interviews and recordings of lectures that dealt with, in the main, the relationship between Scotland, the Irish in Scotland and the Rising in Dublin in 1916.